208. Clinical outcomes of empirical versus pre-emptive broad spectrum antifungal therapy in patients with acute myelogenous leukemia receiving antimold prophylaxis. (15th December 2022) - Oh, Sang-Min; Lee, Chan Mi; Choi, Seong Jin; Lee, Eunyoung; Kang, Chang Kyung; Moon, Song Mi; Choe, Pyoeng Gyun; Song, Kyoung-Ho; Park, Wan Beom; Bang, Ji Hwan; Kim, Eu Suk; Park, Sang Won; et al.
Abstract: Background: Since antimold prophylaxis has been widely used in induction chemotherapy for acute myelogenous leukemia (AML), it should be re-evaluated whether broad spectrum antifungal therapy should be empirically used in prolonged febrile neutropenia. Therefore, we compared clinical outcomes of empirical versus pre-emptive antifungal therapy in patients with AML receiving antimold prophylaxis. Methods: From September 2016 to December 2020, all adult AML patients (≥ 18 years) receiving antimold prophylaxis who had febrile neutropenia for ≥ 4 days during induction or re-induction chemotherapy at Seoul National University Hospital were retrospectively reviewed. They were classified into the empirical group (therapeutic broad spectrum antifungal agents had been used without evidence of invasive fungal infection [IFI]) or the pre-emptive group (antimold prophylaxis had been maintained until the emergence of IFI's evidence). We compared clinical outcomes between the two groups after propensity score matching. Results: A total of 229 chemotherapy episodes, 36 in the empirical group and 193 in the pre-emptive group, were analyzed. In the pre-emptive group, broad spectrum antifungal therapy was administered in 45 (23.3%) episodes. After 1:3 matching with age, gender, induction or re-induction chemotherapy, and worst qSOFA score at febrile neutropenia, incidence of proven or probable IFI (0/36 [0%] in the empirical group vs. 5/97 [5.2%] in the pre-emptive group, P =0.323) and all-cause mortality (3/36 [8.3%] in the empirical group vs. 4/97 [4.1%] in the pre-emptive group, P =0.388) were not different between the two groups. Conclusion: Clinical outcomes of empirical versus pre-emptive broad spectrum antifungal therapy were comparable in patients with AML receiving antimold prophylaxis. Broad spectrum antifungal therapy could be delayed until the emergence of evidence of IFI, in the current era of antimold prophylaxis. Disclosures: All Authors : No reported disclosures.